Thus spoke adolf: nietzsche and the perpetrators of hitler's genocides (2001)
This paper is an attempt to analyse the influence that Nietzsche’s philosophy had on the Nazi bureaucratic apparatus that conducted important parts of the Holocaust. Bauman’s sociological interpretation of the Holocaust will be used to argue that Nietzsche, as a committed anti-moralist, had a profound effect on the bureaucratic perpetrators of the Holocaust. Thus, Nietzsche became the ideological swastika of the Nazi party.